FIST students excel in postgraduate poster competition - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Muhammad Najib, Muhammad Nor (Penerbit UMP, 2011)

(untitled)
The competition was held in conjuction to Postgradute Week (7-9 April 201 1) organized by Centre for Graduates Studies.